TINGKAT PEMAHAMAN DAN FAKTOR KEPATUHAN MINUM OBAT ARV PADA PASIEN HIV/AIDS - Adib Samudra Putra; Saepuddin Saepuddin; Suci Hanifah (Parapemikir : Jurnal Ilmiah Farmasi, 2023)
Patients with HIV/AIDS require long-term therapy, so adherence is a significant thing that needs attention. aim  of this article review is to find out the Level of Understanding and Compliance Factors in Taking ARV Medication in HIV/AIDS Patients. The research was conducted in November 2022 by searching for Indonesian articles related to article reviews with the year of publication 2017-2022 in the Google scholar database using the keyword "HIV/ AIDS”, “adherence to taking ARV medication”, and “HIV understanding. Then found 15 journals related to understanding and factors that influence adherence to taking ARV medication with the correlative analytic research method with a cross sectional approach. After further evaluation, 7 relevant journals were found. Next is done by analysis with the approach. A person's understanding of HIV/AIDS is not influenced by their level of education. Family and social support affects the level of patient adherence to routinely taking ARV drugs. Intensive counseling needs to be given to patients and their families as well as the social environment so that patients with HIV/AIDS can be more compliant in using ARV therapy